Exploring stereotypes of gender and social class representations in The Hunger Games: Catching Fire - Christamaria, Lauretta Althea; Silalahi, Elfrida BR. (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2024)
This study explores the representation of gender and social class stereotypes in The Hunger Games: Catching Fire. The data were collected by analyzing key scenes and dialogues in the movie, focusing on instances that reflect stereotypes. The analysis employed theories of gender and social class stereotypes to examine how these stereotypes are represented and portrayed within the main characters, Katniss Everdeen, President Snow, and Plutarch. The findings reveal that gender stereotypes are more dominant than social class stereotypes in the film. The main female character subverts traditional gender roles, displaying strength and independence in contrast to the conventional portrayal of women as weak and reliant on men. Additionally, social class stereotypes are depicted through discrimination and prejudice against lower-class characters. This research aims to enhance readers’ critical understanding of gender and social class representations, promote gender equality, and encourage respect for social diversity.